MXene@Hydrogel composite nanofibers with the photo-stimulus response and optical monitoring functions for on-demand drug release - Yan, Bing-Yu; Cao, Zhi-Kai; Hui, Chao; Sun, Tian-Cai; Xu, Lei; Ramakrishna, Seeram; Yang, Min; Long, Yun-Ze; Zhang, Jun (Journal of colloid and interface science, 2023)
In this study, we design a heating electrospray during electrospinning to prepare photo-stimulus response composite nanofibers consisting of MXene@Hydrogel. This heating electrospray could maintain the fluid state of MXene@Hydrogel, and spray it during the electrospinning process, so that hydrogel is uniformly distributed which cannot be achieved by the traditional soaking method. Due to the photothermal properties of composite nanofibers, the fluidity of hydrogel can be controlled by light, thus controlling the release rate of drugs. The “on” and “off” state of drug release could be controlled by light. [Display omitted] The photo-stimulus response has the advantage of non-invasiveness, which could be used to control the “on” and “off” of drug release achieving on-demand release. Herein, we design a heating electrospray during electrospinning to prepare photo-stimulus response composite nanofibers consisting of MXene@Hydrogel. This heating electrospray enables to spray MXene@Hydrogel during the electrospinning process, and the hydrogel is uniformly distributed which cannot be achieved by the traditional soaking method. In addition, this heating electrospray can also overcome the difficulty that hydrogels are hard to be uniformly distributed in the inner fiber membrane.The “on” and “off” state of drug release could be controlled by light. Not only near infrared (NIR) light but also sunlight could trigger the drug release, which could benefit outdoor use when cannot find NIR light. Evidence by hydrogen bond has been formed between MXene and Hydrogel, the mechanical property of MXene@Hydrogel composite nanofibers is significantly enhanced, which is conducive to the application of human joints and other parts that need to move. These nanofibers also possess fluorescence property, which is further used to real-time monitor the in-vivo drug release. No matter the fast or slow release, this nanofiber can achieve sensitive detection, which is superior to the current absorbance spectrum method.